Pengetahuan Dan Sikap Calon Pengantin Terhadap Aplikasi Elsimil Di KUA Kecamatan Pahandut - Munanadia, Munanadia (Bunda Edu-Midwifery Journal (BEMJ), 2024)
Stunting in children due to prolonged malnutrition is a form of growth faltering due to the accumulation of inadequate nutrition that lasts from pregnancy to 24 months of age. One specific intervention is carried out by means of nutritional interventions in mothers before and during pregnancy. In this case, the National Population and Family Planning Agency (BKKBN) developed the Elsimil Application, catin must be examined first if there is anemia and malnutrition is encouraged to delay pregnancy until nutrition is sufficient. This application is expected to detect early the potential birth of stunted babies based on the health condition of the catin. based on the results of the health check the application will conduct an automatic assessment to determine the condition of the catin woman is "ideal" or "at risk" for pregnancy and childbirth. This research is descriptive with a Cross Sectional approach conducted at the KUA of Pahandut District with the sampling technique is total sampling of 32 catin couples aiming to provide an overview of how catin's attitudes and behavior towards policies with the ELSIMIL application. Data were collected by the researcher using a questionnaire containing characteristics and nutritional status as well as catin's knowledge and attitude about the ELSIMIL application. Data were analyzed using a descriptive analysis approach of each research variable. Based on the results of the study, it is known that most of the catin's knowledge about the ELSIMIL application is good as much as 62.5%, sufficient knowledge as much as 28.1%, and there are still 9.4% catin with less knowledge about the ELSIMIL application. As for the catin's attitude towards the ELSIMIL application, most of them are positive as much as 84.4%, but there are still 15.6% catin with a negative attitude. This policy should be more often held socialization activities to the community because the ELSIMIL application is filled in 3 months before the wedding and there must be continuous coordination with the accompanying officers consisting of KB Kader, PKK Kader, and Midwives.